2017
DOI: 10.1007/s00125-017-4426-9
|View full text |Cite|
|
Sign up to set email alerts
|

Increased plasma N-glycome complexity is associated with higher risk of type 2 diabetes

Abstract: Aims/hypothesis Better understanding of type 2 diabetes and its prevention is a pressing need. Changes in human plasma Nglycome are associated with many diseases and represent promising diagnostic and prognostic biomarkers. Variations in glucose metabolism directly affect glycosylation through the hexosamine pathway but studies of plasma glycome in type 2 diabetes are scarce. The aim of this study was to determine whether plasma protein N-glycome is changed in individuals who are at greater risk of developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
76
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 23 publications
(23 reference statements)
14
76
1
Order By: Relevance
“…Identified type 2 diabetes risk allele in European‐descent individuals was associated with an increase in ST6GAL1 expression in islets . This finding further corroborates the hypothesis that highly branched N‐glycans (which are also highly sialylated) are associated with higher risk of developing type 2 diabetes . The study investigating the specific linkage of the sialic acid, as discussed previously, has demonstrated that total plasma protein biantennary N‐glycans with α2,6‐linked sialic acid are increased in type 2 diabetes ; further confirming the potential causal relation between α2,6‐linked sialic acid and type 2 diabetes.…”
Section: Type 2 Diabetessupporting
confidence: 82%
See 4 more Smart Citations
“…Identified type 2 diabetes risk allele in European‐descent individuals was associated with an increase in ST6GAL1 expression in islets . This finding further corroborates the hypothesis that highly branched N‐glycans (which are also highly sialylated) are associated with higher risk of developing type 2 diabetes . The study investigating the specific linkage of the sialic acid, as discussed previously, has demonstrated that total plasma protein biantennary N‐glycans with α2,6‐linked sialic acid are increased in type 2 diabetes ; further confirming the potential causal relation between α2,6‐linked sialic acid and type 2 diabetes.…”
Section: Type 2 Diabetessupporting
confidence: 82%
“…Replication cohort comprised individuals with increased levels of HbA1c, incident cases of type 2 diabetes gathered at baseline and controls. Study showed that increased complexity of N-glycan structures (highly branched, galactosylated and sialylated) among total plasma proteins was associated with increased risk of type 2 diabetes development [39]. The same differences were subsequently replicated by the analysis of 820 incident cases of type 2 diabetes in the German part of the .…”
Section: Total Plasma Protein and Igg N-glycan Profiling In Type 2 DImentioning
confidence: 83%
See 3 more Smart Citations